Long-Run Performance Persistence of Investment Funds. Issue 8 (2nd August 2016) - Urbański, Stanisław; Winiarz, Maciej; Urbański, Kacper
ABSTRACT: This article analyzes the long-run persistence of returns and risk of investment in the assets of money, bound, and stock funds recorded on the Polish market in 2000–12. Portfolios of safe, hybrid, and stock classes are formed on the basis of tested funds. The persistence of returns and the Sharpe ratio are investigated in rolled five-year sub-periods, with one year step. Also, persistence in performance is assessed using classic CAPM and Fama and French models, which allow for evaluating management skills. We find the occurrence of the Sharpe ratio long-run persistence of money and bound funds. The study does not explicitly show long-run persistence in hybrid and stock fund portfolios. The CAPM and Fama and French models simulations of returns on stock and hybrid funds indicate varying management skills during five-year periods.